Propionibacterium acnes Is an Unusual Cause of Acute Scrotal Abscess in a Preterm Infant - Naoto Nishizaki; Tadaharu Okazaki; Yu Adachi; Kaoru Obinata; Hiromichi Shoji; Toshiaki Shimizu (Case Reports in Urology)
Acute scrotal abscess is an extremely rare condition in neonates and may mimic testicular torsion. Most of these abscesses have reportedly been due to Staphylococcus and Salmonella spp. infections. We herein report a unilateral acute scrotal abscess in a preterm infant born at 26 weeks in whom Propionibacterium acnes was isolated from the collected scrotal fluid culture. To our knowledge, this is the first case report implicating P. acnes as a causative agent of neonatal scrotal abscess. Based on such findings, P. acnes infection should be considered in differential diagnosis of acute scrotal abscess in neonates, particularly in preterm infants.